Low affinity nerve growth factor receptor binding in normal and Alzheimer's disease basal forebrain. - Treanor, J; Dawbarn, D; Allen, S; MacGowan, S; Wilcock, G (1991)
The binding characteristics of radiolabelled beta-nerve growth factor ([125I]NGF) have been determined on membrane preparations of basal forebrain from Alzheimer's disease (AD) brain and age-matched normal brains. [125I]NGF binds in a specific fashion indicative of a single receptor and is not displaced with microM concentrations of cytochrome c, insulin or epidermal growth factor (EGF). The mean dissociation constant (Kd) and the mean capacity (Bmax) of the NGF receptor were not significantly different between the 5 AD and 5 normal basal forebrain samples examined. Choline acetyltransferase (ChAT) activity was significantly reduced (P less than or equal to 0.001) in AD cerebral cortical samples compared with normal tissue.